Sustainable Supply Chain Management in the South African Manufacturing Industry: Navigating challenges and opportunities through green marketing and ethical consumerism - Anathi, Sokhetye (Acta Carolus Robertus, 2024)
This paper explores sustainable practices in the South African manufacturing industry, with a focus on green marketing and ethical consumerism. It outlines these phrases and their importance in developing sustainable and socially responsible supply chains. The literature study investigates how green marketing focuses on eco-friendly products and consumer perceptions, whereas ethical consumerism emphasizes fair labour practices and ethical sourcing. This paper adopts literature, drawing exclusively from primary sources such as academic journals and publications accessible through databases like Web of Science. The focus is on synthesizing insights from scholarly articles, research papers, and industry reports to examine the interconnections between green marketing and ethical consumerism. The research aims to provide a comprehensive understanding of the current state and implications of green marketing and ethical consumerism in fostering sustainable supply chains within the South African manufacturing sector, solely relying on information derived from scholarly publications. The article delves deeper into the linkages between these theories, emphasizing the need of consumer education, transparency, and industry collaboration. Manufacturers should follow strategic guidelines, such as effective communication and long-term commitment while implementing these practices. The conclusion emphasizes the transformative path to a sustainable future, in which manufacturers play a key role in promoting economic viability as well as beneficial societal and environmental effect.